N-(4-Pyridinium dichromate)-p-Toluenesulphonamide as an Efficient Oxidant for Alcohols Under Mild Condition - Khazaei, Ardeshir; Mehdipour, Ebrahim; Yadegari, Soleiman (Asian Journal of Chemistry, 2010)
N-(4-Pyridinium dichromate)-p-toluenesulphonamide [NPDTS] when reacted with alcohols and converts them to their corresponding carbonyl compounds in good yields under mild conditions.